(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The aim of this research is analysis the effect of the changes in (GDA, g, inflation) at average and standard economic curriculum in composition of the models, depending on SPSS program in analysis, and according to available date from central bank of Iraq and during the period from 2003 to 2018 and by using OLS and estimate of the equation and the results showed a statistical significance relation in incorporeal level 5% and the R2 value equal to 92.1 refer to the changes in independent variables explain 92% of changes of unemployment and the independent variables effect are very limit depend on estimated parameters in the model and respectively (0.986,0.229,-0.060), the research recommended necessity to active the investment spending and diversification of production base and limit unrestricted import, and finding a coordinate base between financial policy and monetary policy to limit of unemployment in Iraq .